Effect of peripheral substitution on the electronic absorption and magnetic circular dichroism (MCD) spectra of metal-free azo-coupled bisphthalocyanine - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
A new azo-coupled bisphthalocyanine is synthesized from the corresponding quinoxaline oxime which can be obtained by the reaction of s-trans-chloroethanedial with N=N conjugated metal-free phthalocyanine. The phthalocyanine is synthesized by the reaction of 4-vitro-o-phenylenediamine with 2-nitro-9,10,16,17,23,24-hexa(hexylthio)phthalocyanine. Novel compounds are characterized by elemental analysis, UV/vis. IR and H-1 NMR, and MALDI-TOF spectroscopy. The effect of the azo units on the position and intensity of the electronic absorption and magnetic circular dichroism (MCD) spectra of the bisphthalocyanine are examined for the N=N conjugated metal-free phthalocyanine. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: ZINC PHTHALOCYANINES; SPECTROSCOPY; TRANS-2,2'-AZOQUINOXALINE; COMPLEXES